Occupants’ Thermal Adaptive Behavior Pattern in Indonesian Residential Buildings - Sri Rahma Apriliyanthi; Tomonori Sakoi; Takashi Nakaya; Tetsu Kubota; Mochammad Donny Koerniawan; Muhammad Nur Fajri Alfata; Akhlish Diinal Aziiz; Fefen Suhedi; Inat Shani Fathuna (Buildings)
Occupants’ adaptive behaviors (OABs) can boost thermal acceptability. This study aims to identify the OAB pattern in the hot-humid region of Indonesia and compare the thermal acceptability percentage of the groups with the identified patterns. Data from an online questionnaire with 3000 respondents were adopted for the analysis of air conditioning (AC), fan, and portable fan usage intensities, along with AC set-point temperature, clo-value, clothing adjustment, and window opening intensity. Hierarchical cluster analysis and logistic regressions were used to distinguish and evaluate OAB patterns. Five groups with various patterns for each AC and naturally ventilated (NV) residence were identified, and similar pattern groups with high clo-values and low thermal acceptability percentages appeared in both residences. The highest window opening intensity for the most active patterns in both AC and NV residences was perceived to be 87% and 91% as time intensity averages. These findings imply a great influence of NV lifestyles with active behavior patterns on improving thermal acceptability for both residences. This study suggests an appropriate OAB strategy to promote a better trade-off between energy consumption and thermal acceptability, such as patterns with a ±25 °C set-point temperature and various OABs in AC residences. Additionally, further investigation into the socio-cultural effect of OABs is necessary.